Neuroscience Analysis in Helping Students with Dyscalculia Understand Mathematics - Aznil Pajri; Yerizon; Ali Asmar (Jurnal Penelitian Pendidikan IPA, 2025)
This study explores the role of neuroscience in addressing dyscalculia and enhancing mathematics education for students with this learning difficulty. The research synthesizes recent findings on the neural mechanisms underlying dyscalculia, focusing on abnormalities in the intraparietal sulcus and prefrontal cortex, which are critical for numerical processing and working memory. Evidence-based strategies, such as multisensory teaching methods and adaptive technologies, were analyzed for their effectiveness in supporting mathematical learning. Advanced neuroimaging techniques like fMRI and EEG were highlighted as tools to monitor real-time brain activity, enabling personalized interventions. The results emphasize the need for tailored approaches that address individual cognitive profiles, as traditional one-size-fits-all methods often fall short. Despite the promise of neuroscience-informed practices, challenges remain in translating these insights into accessible classroom tools due to high costs and limited teacher training. The study concludes that integrating neuroscience into education offers transformative potential but requires scalable solutions and professional development programs for educators. This approach fosters inclusive learning environments that support academic success and emotional well-being for students with dyscalculia.